Implementation of Policies to Enforce Discipline Among Teachers and Students at Muhammadiyah 5 Elementary School, Pekanbaru - Dinda Putri Hasanah; Hafifah Hafifah; Salsa Bila Khotrun Nada; Wardah Yuni Kartika; Sakban Sakban (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study examines the implementation of disciplinary policies for teachers and students at Muhammadiyah 5 Elementary School using interviews and field observations. The goal is to determine the effectiveness of these policies in creating an orderly and conducive learning environment. The data obtained are analyzed qualitatively to describe how the disciplinary policies are implemented and the challenges faced in their implementation. The results indicate that the disciplinary policies are implemented consistently with a persuasive approach by teachers, which has a positive impact on improving student discipline. However, parental involvement and students' internal challenges also influence the policy's outcomes. In conclusion, disciplinary enforcement at Muhammadiyah 5 Elementary School is effective and plays a significant role in shaping student character.